Newspaper photo of Diamond Jubilee: Library's 75th anniversary. (Raton, NM Raton Range., 1987)
Photo of donation of TV and VCR to library by the friends of the library
1 newspaper article with photo of Library Director Betty Llyod, Library board Chairman Robert Skinner and Friends of the Library President Katie Kierst
Master list item #18
File location is in the Raton File Cabinet drawer 3
Keywords: Arthur Johnson Memorial Library. -- Raton, New Mexico; Newspaper article -- Raton, New Mexico; Friends of the library -- Raton, New Mexico; Betty Llyod -- Raton, New Mexico -- Librarian; Robert Skinner -- Raton, New Mexico -- Library Board Chairman; Katie Kierst -- Raton, New Mexico -- Friends of the Library President